African Music. Sandtracks. 2007. Tiris; produced and arranged by Kad and Momo Hafsi. Sandblast Arts. SBCD001. One compact disc. Liner notes in English by Garth Cartwright, with photography by Rif Spahni and Simon Thorpe. - Forss, Matt (International Library of African Music, 2008)
pages: 128-129
Keywords: African Music